2020
DOI: 10.3393/ac.2020.01.16
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Preoperative Pain Education on the Decision to Discharge Patients Following Single-Incision Laparoscopic Appendectomy

Abstract: Purpose: Few studies have analyzed the effects of preoperative pain education on the postoperative decision to discharge. The purpose of this study was to determine the effects of pain education and management on the decision to discharge patients after single-incision laparoscopic appendectomy (SILA). Methods:We analyzed 135 patients who had undergone SILA for acute appendicitis between March 2017 and April 2018 in a single medical center. Of these, 72 (53.3%) patients had received preoperative pain education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The surgeries for patients with complicated appendicitis showing evidence of perforation and gangrenous appendixes in our study were more frequently performed in another worldwide study (perforation: 25 of 101, 24.8% vs. 255 of 3,631, 7.0%) [24]. As our institution is a tertiary referral medical center, patients with simple appendicitis are often transferred to a local clinic when ever there is shortage of surgeons or anesthetists [22]. However, patients with severe appendicitis, such as perforated appendicitis, are likely to undergo surgery at our hospital.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…The surgeries for patients with complicated appendicitis showing evidence of perforation and gangrenous appendixes in our study were more frequently performed in another worldwide study (perforation: 25 of 101, 24.8% vs. 255 of 3,631, 7.0%) [24]. As our institution is a tertiary referral medical center, patients with simple appendicitis are often transferred to a local clinic when ever there is shortage of surgeons or anesthetists [22]. However, patients with severe appendicitis, such as perforated appendicitis, are likely to undergo surgery at our hospital.…”
Section: Discussionmentioning
confidence: 67%
“…Our ERAS program for patients included the preoperative pain education, effective pain control, opioid minimization, and early diet. Due to the diagnosis-related group (DRG) systems for patients undergoing appendectomy, some patients decline postoperatively to be discharged from the hospital until complete recovery; however, preoperative pain education has shortened the length of hospital stay after surgery [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 18 In addition, development of multimodal pain managements, such as rectus sheath block and preoperative pain education, can contribute to the reduction in LOH. 19 20 In a recently conducted randomized clinical trial, it was demonstrated that enhanced recovery after surgery program can be applied in the field of laparoscopic appendectomy. In this program, patients advanced to their regular diet in 6 hours after surgery.…”
Section: Discussionmentioning
confidence: 99%